Dynamic Tracking Human Mesenchymal Stem Cells Tropism following Smoke Inhalation Injury in NOD/SCID Mice. (20th September 2016) - Song, MeiJuan; Lv, Qi; Zhang, XiuWei; Cao, Juan; Sun, ShuLi; Xiao, PeiXin; Hou, ShiKe; Ding, Hui; Liu, ZiQuan; Dong, WenLong; Wang, JinQiang; Wang, Xue; et al.
Abstract : Multiple preclinical evidences have supported the potential value of mesenchymal stem cells (MSCs) for treatment of acute lung injury (ALI). However, few studies focus on the dynamic tropism of MSCs in animals with acute lung injury. In this study, we track systemically transplanted human bone marrow-derived mesenchymal stem cells (hBMSCs) in NOD/SCID mice with smoke inhalation injury (SII) through bioluminescence imaging (BLI). The results showed that hBMSCs systemically delivered into healthy NOD/SCID mouse initially reside in the lungs and then partially translocate to the abdomen after 24 h. Compared with the uninjured control group treated with hBMSCs, higher numbers of hBMSCs were found in the lungs of the SII NOD/SCID mice. In both the uninjured and SII mice, the BLI signals in the lungs steadily decreased over time and disappeared by 5 days after treatment. hBMSCs significantly attenuated lung injury, elevated the levels of KGF, decreased the levels of TNF- α in BALF, and inhibited inflammatory cell infiltration in the mice with SII. In conclusion, our findings demonstrated that more systemically infused hBMSCs localized to the lungs in mice with SII. hBMSC xenografts repaired smoke inhalation-induced lung injury in mice. This repair was maybe due to the effect of anti-inflammatory and secreting KGF of hMSCs but not associated with the differentiation of the hBMSCs into alveolar epithelial cells.